(untitled) (American Journal of Islam and Society, 2009)
On 16 October 2009, the Institute of Global Cultural Studies (IGCS) at Binghamton, jointly with the Association of Muslim Social Scientists of North America (AMSS), sponsored a symposium in Binghamton University’s Mandela Hall on “The Obama Administration and US Relations with theMuslimWorld: Prospects, Progress and Lingering Skepticism.” The presentations addressed Iran’s nuclear program, Arab-Israeli relations, Iraq and Afghanistan, Darfur, and studies comparing Obama with Malcolm X and Japan’s new prime minister Yukio Haroyama. Inevitably, there was also some debate as to whether Obama’s Nobel Peace Prize was legitimately earned or premature ...